Study of antimicrobial activity and atomic force microscopy imaging of the action mechanism of cashew tree gum - Campos, Débora A.; Ribeiro, Alexandra C.; Costa, Eduardo M.; Fernandes, João C.; Tavaria, Freni K.; Araruna, Felipe Bastos; Eiras, Carla; Eaton, Peter; Leite, José Roberto S.A.; Manuela Pintado, M. (Carbohydrate polymers, 2012)
► Pure gum presented higher activity against all studied bacteria with the exception of L. acidophilus. ► Crude gum presented activity only against Gram-positive bacteria and at higher CMI values than pure gum. ► Only crude gum presented bactericidal concentrations and only for Gram positive bacteria. ► Optical density measures showed that cashew gum maintained its inhibitory activity over time. ► AFM imaging showed that 10mg/ml of pure cashew gum acted upon the cell wall leading to the collapse of the cellular structure. The aim of this work was to evaluate the antimicrobial potential of two grades of cashew tree gum (crude and purified) against eight microorganisms and to analyze the mechanism of cashew tree gum antimicrobial action via atomic force microscopy (AFM) imaging. The results indicated strong antimicrobial properties of pure cashew tree gum against all tested microorganisms, except for Candida albicans and Lactobacillus acidophilus. On the other hand crude cashew gum showed antimicrobial activity only against Gram-positive bacteria (MRSA, MSSA, Listeria innocua and Enterococcus faecium). Atomic force microscopy imaging showed that pure cashew tree gum lead to bacterial cell collapse. In conclusion cashew tree gum presented relevant antimicrobial activity against most of the studied bacteria, and the purification of the cashew gum affected its antimicrobial spectrum.